Pregnancy Outcome of Multiparous Women Aged over 40 Years. (29th December 2012) - Ates, Seda; Batmaz, Gonca; Sevket, Osman; Molla, Taner; Dane, Cem; Dane, Banu
Abstract : Objective . The aim of this study was to evaluate the effect of maternal age on prenatal and obstetric outcome in multiparaous women. Materials and Methods . A retrospective case control study was conducted, including women aged 40 years and over (study group, n = 97 ) who delivered at 20 week's gestation or beyond and women aged 20–29 years (control group, n = 97 ). Results . The mean age of women in the study group was41.2 ± 1.7 years versus25.4 ± 2.3 years in the control group. Advanced maternal age was associated with a significantly higher rate of hypertension, diabetes mellitus, fetal complication, and 5-minute Apgar scores <7 (P < 0.05 ). Caeserean section rate, incidence of placental abruption, preterm delivery, and neonatal intensive care unit admission were more common in the older group, but the differences were not statistically significant. Conclusions . Advanced maternal age is related to maternal and neonatal complications.